2009
DOI: 10.1128/jvi.00179-08
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Linker between the Methyltransferase and Helicase Domains of Potato Virus X Replicase Is Involved in Homologous RNA Recombination

Abstract: Recombination in RNA viruses, one of the main factors contributing to their genetic variability and evolution, is a widespread phenomenon. In this study, an in vivo assay to characterize RNA recombination in potato virus X (PVX), under high selection pressure, was established. Agrobacterium tumefaciens was used to express in Nicotiana benthamiana leaf tissue both a PVX isolate labeled with green fluorescent protein (GFP) containing a coat protein deletion mutation (⌬CP) and a transcript encoding a functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Recently, the pentapeptide scanning mutagenesis of the PVX replicase indicated that the hydrophilic linker between the N-terminal methyltransferase (MT) and the C-terminal Hel-polymerase (HEL-POL) domains possesses a distinct recombination function vital www.annualreviews.org • RNA Recombination in Plant Viruses for maintenance of genome integrity (37). The pentapeptide insertion in two replicase amino acid positions 430 and 434 interfered with the dynamic interaction necessary for a possible template switch of the molecule.…”
Section: Cis-acting Replication Signal (Re): a 150-nt Subset Of The Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the pentapeptide scanning mutagenesis of the PVX replicase indicated that the hydrophilic linker between the N-terminal methyltransferase (MT) and the C-terminal Hel-polymerase (HEL-POL) domains possesses a distinct recombination function vital www.annualreviews.org • RNA Recombination in Plant Viruses for maintenance of genome integrity (37). The pentapeptide insertion in two replicase amino acid positions 430 and 434 interfered with the dynamic interaction necessary for a possible template switch of the molecule.…”
Section: Cis-acting Replication Signal (Re): a 150-nt Subset Of The Bmentioning
confidence: 99%
“…During in vitro transcription with purified viral RNA-dependent RNA polymerase (RdRp) and derivatives of viral RNAs, both parental and recombined type products are synthesized. ORFs are marked in green (a,b), noncoding regions are marked with gray lines, and red indicates mutations.Other recombination systems were developed relying on satellite and genomic RNAs of Turnip crinkle virus (TCV)(149), or defective interfering RNAs (DI RNAs) of Tomato bushy stunt virus (TBSV), Cucumber necrosis virus (CNV)(144), and Potato virus X (PVX)(37,38). These systems employed at least two parental RNA molecules with one component carrying a deleterious mutation.…”
mentioning
confidence: 99%
“…Total protein was extracted from leaves by grinding samples with extraction buffer (4 M urea, 4% SDS, 0.2 M dithiothreitol, 20% glycerol, 0.2 M Tris-HCl, pH 6.8, and 0.04% bromphenol blue; Draghici and Varrelmann, 2009) or standard protein extraction buffer (100 mM Tris-HCl, pH 7.5, 10 mM KCl, 0.4 M Suc, 10% glycerol, and 10 mM phenylmethylsulfonyl fluoride; Sambrook et al, 1989) and quantified using Bradford Reagent (Sigma-Aldrich). Thirty micrograms of protein for each sample was loaded onto a 4% to 20% precast gradient or 10% SDS-PAGE gels (Bio-Rad) and electroblotted to Hybond-P (GE Healthcare) using standard protocols (Sambrook et al, 1989).…”
Section: Immunoblot Analysesmentioning
confidence: 99%
“…A mutation within the polymerase domain of 2a inhibited heteroduplex-mediated non-HR while increasing homologous crossovers (Figlerowicz et al, 1997). The hydrophilic linker between the N-terminal MT and the C-terminal HELpolymerase (HEL-POL) domains of the PVX replicase possesses a distinct recombination function vital for maintenance of genome integrity (Draghici and Varrelmann, 2009). The hydrophilic linker between the N-terminal MT and the C-terminal HELpolymerase (HEL-POL) domains of the PVX replicase possesses a distinct recombination function vital for maintenance of genome integrity (Draghici and Varrelmann, 2009).…”
Section: B Factors Affecting Rna Recombinationmentioning
confidence: 99%